Truman and Pendergast - Ferrell, Robert H. (University of Missouri Press, 1999)
Chronicles the political relationship of Harry S. Truman and Thomas J. Pendergast. Pendergast was considered the "boss of Kansas City". His personal and political corruption brought about his downfall and imprisonment for tax evasion in 1939. Truman nearly lost his Senate seat in the Democratic primary of 1940 because of his association with Pendergast as well as President Franklin D. Roosevelt's endorsement of Lloyd D. Stark, then governor of Missouri.